2018
DOI: 10.1080/03007995.2018.1541445
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulation therapy and subsequent risk of venous thromboembolism in atrial fibrillation patients

Abstract: Objective: Oral anticoagulation (OAC) prescribed to AF patients for the prevention of cardioembolic complications likely has the added benefit of preventing venous thromboembolism (VTE). We evaluated, among AF patients who are anticoagulated, whether type of OAC was associated with subsequent VTE risk. Methods: Non-valvular AF patients prescribed OACs between 2010 and September 2015 were identified via the MarketScan administrative claims databases. OACs included warfarin and direct OACs (DOACs: dabigatran, ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
12
0
1
Order By: Relevance
“…In sensitivity analyses, we adjusted for empirically‐defined high‐dimensional propensity scores (HDPS) (Schneeweiss et al , ) instead of the propensity scores created using the pre‐specfied comorbidities and medications. We have detailed our MarketScan HDPS approach previously (Lutsey et al , ). Separate high‐dimensional propensity scores were calculated for each of the three comparisons, and for the periods before and after ICD‐10 adoption (1 October 2015).…”
Section: Methodsmentioning
confidence: 99%
“…In sensitivity analyses, we adjusted for empirically‐defined high‐dimensional propensity scores (HDPS) (Schneeweiss et al , ) instead of the propensity scores created using the pre‐specfied comorbidities and medications. We have detailed our MarketScan HDPS approach previously (Lutsey et al , ). Separate high‐dimensional propensity scores were calculated for each of the three comparisons, and for the periods before and after ICD‐10 adoption (1 October 2015).…”
Section: Methodsmentioning
confidence: 99%
“…There was no difference in VTE risk when comparing rivaroxaban to warfarin (1.01. (0.87-1.19)) [33]. Also, in a large cohort study, the risk of AF after a PE episode was attenuated after adjustment for anticoagulant therapy [5].…”
Section: Gaps In Evidencementioning
confidence: 99%
“…Five studies concerned elderly patients specifically (ie, ≥65 years old), 19 21 23–25 two included adults ≥45 years old 33 40 and one study included patients between 30 and 100 years of age. 44 The other studies included all adults with atrial fibrillation (it was assumed that if no further age specification was provided, ‘adults’ meant that all >18 years old were included).…”
Section: Resultsmentioning
confidence: 99%
“…However, in one of the articles, an extensive rationale and selection procedure of covariates that were included in the analysis was provided. 33 In three other studies, the authors selected covariates based on medical knowledge on risk factors with reference to earlier published studies. 31 39 52 In one other study, it was reported that sociodemographic and clinical characteristics that were associated with treatment initiation and the risk of major bleeding were included in the model to adjust for differences across cohorts, without further explanation or reference.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation